2015
DOI: 10.1021/acs.chemrestox.5b00452
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenine Signaling Increases DNA Polymerase Kappa Expression and Promotes Genomic Instability in Glioblastoma Cells

Abstract: Over-expression of the translesion synthesis polymerase (TLS pol) hpol κ in glioblastomas has been linked to a poor patient prognosis; however, the mechanism promoting higher expression in these tumors remains unknown. We determined that activation of the aryl hydrocarbon receptor (AhR) pathway in glioblastoma cells leads to increased hpol κ mRNA and protein levels. We blocked nuclear translocation and DNA binding by the AhR in glioblastoma cells using a small-molecule and observed decreased hpol κ expression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 42 publications
2
50
1
Order By: Relevance
“…The loss of pChk1 signal that accompanied TDO inhibition is interesting given that hpol k has been shown to help activate the Rad17-arm of the ATR signaling cascade leading to phosphorylation of the Chk1 kinase. Previously we observed down-regulation of hpol k in response to TDO inhibition (13). In this respect, the reduction in pS345 Chk1 when TDO was inhibited might be due to suppression of hpol k/Rad17-mediated activation of ATR (16,17).…”
Section: Inhibition Of Tdo Leads To Diminished Resolution Of Rs Inducmentioning
confidence: 79%
See 1 more Smart Citation
“…The loss of pChk1 signal that accompanied TDO inhibition is interesting given that hpol k has been shown to help activate the Rad17-arm of the ATR signaling cascade leading to phosphorylation of the Chk1 kinase. Previously we observed down-regulation of hpol k in response to TDO inhibition (13). In this respect, the reduction in pS345 Chk1 when TDO was inhibited might be due to suppression of hpol k/Rad17-mediated activation of ATR (16,17).…”
Section: Inhibition Of Tdo Leads To Diminished Resolution Of Rs Inducmentioning
confidence: 79%
“…Previously, we showed that modulation of the KP affected the expression of the translesion synthesis (TLS) enzyme DNA polymerase kappa (hpol k) (13). Treating GBM-derived cell lines with an inhibitor of TDO lowered hpol k expression and led to a diminished level of micronuclei (MN).…”
Section: Introductionmentioning
confidence: 99%
“…The oncological relevance of pol κ and pol η in cancer is most firmly established concerning response to treatment. Upregulation of pol κ confers resistance to temozolomide in glioblastoma, 34,35 and upregulation of pol η to platinum drugs in HNSCC, lung, gastric adenocarcinomas, and ovarian cancers. [36][37][38] Contrary to our results, low levels of POLK were previously observed in CRC.…”
Section: Associations Of Dsbr Iclr and Ddt/tls Key Components Witmentioning
confidence: 99%
“…113 Furthermore, blocking KYN signaling in GBM-derived cells with a small-molecule inhibitor of TDO (680C91) led to a dramatic decrease in hpol κ protein levels. 113 …”
Section: Kyn Activation Of Ahr Promotes Up-regulation Of Hpol κmentioning
confidence: 99%
“…TDO activity -> AhR signaling -> hpol κ expression). 113 It is reasonable to assume that KYN signaling will be found to affect additional DNA damage and replication stress response factors. If such an assumption proves true, then it would go some way towards explaining why blocking KYN signaling has been found to act synergistically with genotoxic anti-cancer drugs in multiple models of cancer.…”
Section: Kyn Activation Of Ahr Promotes Up-regulation Of Hpol κmentioning
confidence: 99%